2015
DOI: 10.1371/journal.pone.0137305
|View full text |Cite
|
Sign up to set email alerts
|

Oral TNFα Modulation Alters Neutrophil Infiltration, Improves Cognition and Diminishes Tau and Amyloid Pathology in the 3xTgAD Mouse Model

Abstract: Cytokines such as TNFα can polarize microglia/macrophages into different neuroinflammatory types. Skewing of the phenotype towards a cytotoxic state is thought to impair phagocytosis and has been described in Alzheimer’s Disease (AD). Neuroinflammation can be perpetuated by a cycle of increasing cytokine production and maintenance of a polarized activation state that contributes to AD progression. In this study, 3xTgAD mice, age 6 months, were treated orally with 3 doses of the TNFα modulating compound isoindo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 60 publications
2
33
0
Order By: Relevance
“…Involvement in AD pathology TNF-α TNF-α is involved in inducing acute phase inflammation and is elevated in AD serum, cerebrospinal fluid (CSF) and cortex (Tarkowski et al, 1999(Tarkowski et al, , 2003. Anti-TNF-α treatment reduces Aβ deposition, behavioral impairments, and inflammation in AD animal models suggesting TNF-α is detrimental factor in AD (Russo et al, 2012;Tweedie et al, 2012;Detrait et al, 2014;Gabbita et al, 2015). However, one study suggests that TNF-α expression in APP transgenic mice at early stage induces glial uptake of Aβ (Chakrabarty et al, 2011).…”
Section: Cytokinementioning
confidence: 99%
“…Involvement in AD pathology TNF-α TNF-α is involved in inducing acute phase inflammation and is elevated in AD serum, cerebrospinal fluid (CSF) and cortex (Tarkowski et al, 1999(Tarkowski et al, , 2003. Anti-TNF-α treatment reduces Aβ deposition, behavioral impairments, and inflammation in AD animal models suggesting TNF-α is detrimental factor in AD (Russo et al, 2012;Tweedie et al, 2012;Detrait et al, 2014;Gabbita et al, 2015). However, one study suggests that TNF-α expression in APP transgenic mice at early stage induces glial uptake of Aβ (Chakrabarty et al, 2011).…”
Section: Cytokinementioning
confidence: 99%
“…Further, TNF-α was described to induce APP mRNA expression in a dose-dependent manner via nuclear factor k B activation [ 82 ]. Consistently, TNF-α modulation decreased fibrillar amyloid accumulation [ 83 ] and chronic administration of TNF-α lowering agents decreased APP levels, soluble Aβ 1-42 and Aβ deposition in old 3xtg AD mice [ 84 ]. However, expression of murine TNF-α in APP tg mice at early stage rendered in attenuated Aβ 1-42 and Aβ 1-40 plaque burden and deposition, without difference in APP levels [ 85 ].…”
Section: Cytokines and Chemokines In App 
Processingmentioning
confidence: 98%
“…High levels of TNF-α have also been identified in murine models of AD that resemble the classical behavioral abnormalities of the disease in humans (Gabbita et al, 2012;Kinney et al, 2018). Blocking the TNF-α pathway decreases central immune infiltration and prevents AD neurochemical and behavioral phenotypes Prasad Gabbita et al, 2015), suggesting that central-peripheral cross-talk may be implicated in the disease. Notably, experimental studies using transgenic AD models have demonstrated that non-steroidal anti-inflammatory drugs (NSAIDs) can reduce AD pathology (Kinney et al, 2018).…”
Section: Active Immunity In Alzheimer Disease (Ad)mentioning
confidence: 99%